2015
DOI: 10.1016/j.ahj.2015.05.012
|View full text |Cite
|
Sign up to set email alerts
|

National assessment of early β-blocker therapy in patients with acute myocardial infarction in China, 2001-2011: The China Patient-centered Evaluative Assessment of Cardiac Events (PEACE)–Retrospective AMI Study

Abstract: Background Since 2007, clinical practice guidelines have recommended beta-blocker therapy early in the course of acute myocardial infarction (AMI) for patients who are not at high risk for complications. Our objective was to perform a national quality assessment of early beta-blocker use during hospitalization for AMI over the past decade in China. Methods We conducted medical record review of a nationally representative sample of patients admitted to Chinese hospitals with AMI and studied those without abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Beta-blocker therapy has been recommended in the course of MI for patients who are not at high risk for complications. It has revealed that metoprolol is the most frequently used beta-blocker in MI patients in China [ 23 ]. Daily CHD counts were stratified by gender and age groups (41–65 years, and >65 years).…”
Section: Methodsmentioning
confidence: 99%
“…Beta-blocker therapy has been recommended in the course of MI for patients who are not at high risk for complications. It has revealed that metoprolol is the most frequently used beta-blocker in MI patients in China [ 23 ]. Daily CHD counts were stratified by gender and age groups (41–65 years, and >65 years).…”
Section: Methodsmentioning
confidence: 99%
“…However, the dosing of β-blockers such as Met in the clinic varied markedly, often falling short of guideline recommendations. A national assessment of early β-blocker therapy in patients with AMI in China’s PEACE study reported substantial underuse of early β-blocker therapy in ideal candidates with AMI from 2001 to 201135. A study published in 2021 also reported that the early use of oral β-blockers in acute coronary syndrome patients was generally insufficient, with huge differences among different hospitals in China36.…”
Section: Discussionmentioning
confidence: 99%
“…[14] However, due to lack of a specific clinical pathway as a guide, the specific usage of metoprolol still was a practical challenge for clinicians, since the use of beta-blockers was not standardized in terms of dosage and titration method. [31][32][33] The lack of recognition and acceptance of the specific MSDP may result in different practice patterns in different institutions, often fostering potential sub-optimal HR management with clinicians' conservative betablocker titration. The reasonable dosage of metoprolol in ACS patients has been controversial in different reports.…”
Section: Discussionmentioning
confidence: 99%